THE BIRTH OF THE EMPIRICAL TURN IN BIOETHICS - Borry, Pascal (Bioethics, 2005)
Since its origin, bioethics has attracted the collaboration of few social scientists, and social scientific methods of gathering empirical data have remained unfamiliar to ethicists. Recently, however, the clouded relations between the empirical and normative perspectives on bioethics appear to be changing. Three reasons explain why there was no easy and consistent input of empirical evidence into bioethics. Firstly, interdisciplinary dialogue runs the risk of communication problems and divergent objectives. Secondly, the social sciences were absent partners since the beginning of bioethics. Thirdly, the meta-ethical distinction between ‘is’ and ‘ought’ created a ‘natural’ border between the disciplines. Now, bioethics tends to accommodate more empirical research. Three hypotheses explain this emergence. Firstly, dissatisfaction with a foundationalist interpretation of applied ethics created a stimulus to incorporate empirical research in bioethics. Secondly, clinical ethicists became engaged in empirical research due to their strong integration in the medical setting. Thirdly, the rise of the evidence-based paradigm had an influence on the practice of bioethics. However, a problematic relationship cannot simply and easily evolve into a perfect interaction. A new and positive climate for empirical approaches has arisen, but the original difficulties have not disappeared.